Adapted use of fluorescence map in commercial equipment for characteristic x-ray transmittance measurements. (December 2021) - Souza, Lucas C.; Silva, Luisa D.; Oliveira, Davi F.; Anjos, Marcelino J.; Goncalves, Elicardo A.S.
Abstract: In this work, a commercial micro-XRF mapping equipment was adapted to, through data processing, map the characteristic X-ray transmittance throughout samples. The main difference for conventional tests is the production of characteristic x-rays on a metal base, and its detection on the other side of the sample. The transmittance measure can, therefore, be used to estimate, through equation systems, the layer thickness of each material that makes the sample. Samples of radiographic films were used, where the small thicknesses and the great difference in radiopacity between the materials (polyester and silver) are favorable for data acquisition. The results obtained show thickness maps whose values can be checked by other tools, such as micrometers. Such an approach can be extended to cases with more layers, but this directly implies the number of equations to be solved. The applicability can be used in many areas, depending on conditions of material and acquisition.